Role of Astroglial Hemichannels and Pannexons in Memory and Neurodegenerative Diseases - Orellana, Juan A.; Retamal, Mauricio A.; Moraga-Amaro, Rodrigo; Stehberg, Jimmy (Frontiers in Integrative Neuroscience, 2016)
Under physiological conditions, astroglial hemichannels and pannexin channels allow the release of gliotransmitters from astrocytes. These gliotransmitters are critical in modulating synaptic transmission, plasticity and memory. However, recent evidence suggests that under pathological conditions, they may be central in the development of various neurodegenerative diseases. Here we review current literature on the role of astroglial hemichannels and pannexin channels in memory, stress and the development of neurodegenerative diseases, and propose that astroglial connexin hemichannels and pannexin channels are not only crucial for normal brain function, including memory, but also a potential target for the treatment of neurodegenerative diseases.